Interconnected network of ultrafine MnO2 nanowires on carbon cloth with weed-like morphology for high-performance supercapacitor electrodes. (1st April 2018) - Xu, Zhihui; Sun, Shishuai; Cui, Wen; Lv, Jiang; Geng, Yaohui; Li, Hui; Deng, Jiachun
Abstract: A binder-free electrode of ultrafine MnO2 nanowires grown on the carbon cloth (CC) were fabricated by simple hydrothermal method, exhibiting the interconnected network with weed-like morphological feature. The unique pore structure has a large interface surface area, and allows rapid electrolyte diffusion through its hollow/open framework and fast electron transfer though the carbon skeleton. As an electrode for supercapacitors, the ultrafine MnO2 nanowires grown on the CC (ultrafine MnO2 nanowires@CC) exhibit a high specific capacitance (1174.3 F g −1 at the moderate current density of 2 A g −1 ), excellent rate property (stabilize at 927 F g −1 as the current density increases to 40 A g −1 ), and good cycling stability (a negligible 0.1% decay in specific capacitances after 10, 000 cycles).